Effects of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Herd, Lauren; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
An experiment was conducted to measure the effects of varied Gleptoforte dosage on nursing piglet performance. There has been extensive research in determining the optimal dosage of iron dextran to prevent anemia in baby pigs, but little research has been conducted to determine the optimal dosage of Gleptoforte, another iron supplement containing gleptoferron, in baby pigs. A total of 28 litters were utilized for the study, 12 pigs from each litter, for a total of 336 pigs. Six barrows and six gilts from each litter were randomly assigned to one of 6 experimental treatments; one barrow and one gilt per treatment. These treatments included: 1) a negative control of 0 mg injected Gleptoforte, 2) 50 mg, 3) 100 mg, 4) 150 mg, 5) 200 mg, and 6) 200 mg at birth + 100 mg booster at d11 of farrowing. Pig weights were collected at processing (d3), midway (d11), and at weaning. These weights were used to determine ADG for each time interval. Blood was collected from one barrow per treatment per litter for measurement of hematological parameters on the day of processing (d3), midway (d11), and weaning (d21). The hematological parameters measured included: hemoglobin, hematocrit, serum Fe, and Total Iron Binding Capacity (TIBC). An alpha value of 0.05 was used. ADG increased (P=0.001) in the farrowing house as the dosage of Gleptoforte was increased to 100 mg, not increasing any further beyond 100 mg. D21 body weight improved (P=0.001) as dosage was increased to 100 mg as well. There was no evidence of improved performance in the 200 mg + 100 mg treatment when compared to the 200 mg treatment alone. However, hematological parameters measured improved with the 200 mg + 100 mg treatment when compared to the 200 mg treatment. Hemoglobin and value at d21 was significantly different (P=0.011) between the 200 mg treatment and the 200 mg + 100 mg treatment. Also at d21, between the 200 mg and the 200 mg + 100 mg treatments, there was a significant difference (P=0.046) in hematocrit value. The administration of 100 mg of Gleptoforte resulted in the greatest growth performance of pigs in the farrowing house.
Keywords: Fall 2017